Everything is not enough : a novel - Akinmade-Akerström, Lola (In every mirror she's black, 2023)
"Can a career woman truly have it all? Powerful marketing executive Kemi Adeyemi has finally found the man she needs, but Tobias Wikström thinks she's the most selfish woman he has ever met for asking him to give up his life in Sweden and move to the US for her own comfort. Will Kemi be forced to stay if she wants to keep him while chipping away at her hard-earned career? As things begin to sour and challenge her relationship with Tobias, someone else moves back into the picture. Can having it all be a gilded cage? Looking into divorce in Sweden isn't what former model-turned-flight attendant Brittany-Rae von Lundin anticipated. Only jointly owned assets are split evenly between couples. Brittany gave up her career and came with nothing into Jonny's kingdom. Having had a child with him, her greatest fear for Maya includes being cut off from the resources she's become accustomed to. With a man obsessed with a ghost, trying to get away isn't going to be easy. And the deeper she digs into his past, the darker the secrets she unravels. Can you run from your past to have it all? After fleeing her home through a client to seek a new life in Sweden, Yasmiin finds love in the arms of Yagiz Çelik while carving out her own small corner. But as someone from her past forces Yasmiin to become a caretaker before she's ready, she now must confront and move beyond her teenage history, while following her dreams of becoming a makeup artist. Everything Is Not Enough follows the loosely intertwined and messy lives of Kemi, Brittany, and Yasmiin as they interrogate themes of place, prejudice, and patriarchy in Europe, proving--yet again--that Lola Akinmade Åkerström is the next great voice of nuanced contemporary women's fiction." -- Jacket flap